Possible sources of hydrothermal activity and mud volcanism in southern Sakhalin inferred from local earthquake seismic tomography. (12th May 2017) - Koulakov, Ivan; Serdyukov, Aleksander S.; Konovalov, Alexey V.; Mikhailov, Valentin I.; Safonov, Dmitry A.; Duchkov, Anton A.; Al‐Arifi, Nassir; El Khrepy, Sami
Abstract: We present the first seismic model of the crust beneath Sakhalin based on P and S‐wave arrival time data from local earthquakes. Based on the results of numerous synthetic tests, we conclude that this model has fair horizontal and vertical resolution to 20–25 km depth. At shallow depths, seismic anomalies are clearly associated with known geological structures, such as the high‐velocity Paleozoic Susunai block and the low‐velocity Cenozoic fold belts along the West Sakhalin Mountains. In vertical sections, we observe westward underthrusting of the Susunai block to a distance of at least 70 km, which may represent the regional compression and considerable crustal shortening in this area. Based on the tomography results, we hypothesize about the origin of the mud volcanism in southern Sakhalin. We propose that because of the general westward underthrusting regime in Sakhalin, hydrocarbon‐rich shelf sediments may be entrained to considerable depths under the rigid Susunai block, which serves as a nonpermeable cover. The released gases find the weakest zones around the Susunai block and along the Tym‐Poronay Fault and escape to the surface to form the South Sakhalin and Lesnovsky mud volcano fields. Plain Language Summary: Sakhalin is a large island located in the Russian Far East in a zone of strong seismic activity. In Sakhalin, there are several mud volcanoes, two of which are among the largest ones in the world. In the paper, we present the first seismic model of the crust beneath Southern Sakhalin obtained from tomographic inversion of travel times of seismic waves from local earthquakes. The derived tomographic model reveals structures that are similar to those of a subduction complex, but in miniature. We observe a high‐velocity structure with an inclined "mini slab" dipping down to the depth of ∼20 km, which is accompanied by strong seismic activity. Above this anomaly, we find mud volcanoes (a "mini volcanic arc"). Based on this model, we hypothesize that the original cause of mud volcanism in southern Sakhalin is associated with westward dipping of hydrocarbon‐rich sediments of the eastern shelf underneath the island. As a result of this process, the hydrocarbon gases are accumulated at a depth of ∼20 km beneath the Paleozoic Susunai block, which serve as a nonpermeable cover. After reaching a critical amount, the gases escape along the Susunai block borders and form zones of geothermal activity and mud volcanism. Key Points: We present the first tomography model of the crust beneath southern Sakhalin Westward dipping structures indicate longitudinal shortening of Sakhalin Mud volcanism sources are located beneath the rigid Susunai block at 15–20 km depth